General Assembly of the FIEP and a homage to its president during the world Congress of physical education (Fiep Bulletin - online, 2015)
The FIEP held its general Assembly in the Frame-work of the imposing world Congress of physical Education Organized in Madrid from 13th to 17th September 1966, by the National Direction of Physical Education and Sports in Spain and the FIEP the Meeting were carried out in the International Hall of the National Institute of Physical Education.